2011
DOI: 10.1021/nn200182x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes Deliver Peptide Antigen into Dendritic Cells and Enhance IgG Responses to Tumor-Associated Antigens

Abstract: We studied the feasibility of using single-wall carbon nanotubes (SWNTs) as antigen carriers to improve immune responses to peptides that are weak immunogens, a characteristic typical of human tumor antigens. Binding and presentation of peptide antigens by the MHC molecules of antigen presenting cells (APCs) is essential to mounting an effective immune response. The Wilm’s tumor protein (WT1) is upregulated in many human leukemias and cancers and several vaccines directed at this protein are in human clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(133 citation statements)
references
References 42 publications
3
126
0
4
Order By: Relevance
“…81 It is also possible to decorate CNTs with other nanoparticles, such as silver or gold, 82 carbohydrate molecules, 49,83,84 or peptides. 85 This property makes CNTs efficient when it comes to being as similar as possible to the ECM. It is through the implantation of desirable molecules on the nanotube surface that can promote the interconnection between the numerous pores of the support, in order to obtain a more integrated network.…”
Section: Similarity Of Nanotubes With Ecmmentioning
confidence: 99%
“…81 It is also possible to decorate CNTs with other nanoparticles, such as silver or gold, 82 carbohydrate molecules, 49,83,84 or peptides. 85 This property makes CNTs efficient when it comes to being as similar as possible to the ECM. It is through the implantation of desirable molecules on the nanotube surface that can promote the interconnection between the numerous pores of the support, in order to obtain a more integrated network.…”
Section: Similarity Of Nanotubes With Ecmmentioning
confidence: 99%
“…Their results showed that this derivative, together with ovalbumin and an adjuvant, elicited high virus-neutralizing antibody responses in comparison with the non-conjugated peptide. Since this work, the advantages of immunization with proteins and 95 peptides using CNTs have occasionally been confirmed, [55][56][57][58] but, to the best of our knowledge, no evidence of an enhancement in the immune response and antibody production against small molecules using CNTs as vehicles has been reported. The production of antibodies displaying highaffinity and specificity to haptens is an important biotechnological research field because tailor-made binders can be used to develop immunoassays and biosensors for targets such as medicinal drugs, 100 pesticides, drugs of abuse, environmental contaminants, food additives, hormones, toxins, etc.…”
Section: Introductionmentioning
confidence: 96%
“…In order to enhance the efficacy of TCV, the oxidized MWCNTs can be covalently coupled with tumor lysate proteins by an amide bond. On the other hand, Villa et al have developed the capacity of SWCNTs to act as antigen presenting carries to increase the response to weak immunogenic peptides [117]. The Wilms tumor protein (WT1) was covalently conjugated with SWCNTs, and this modification makes it become a vaccine target for many human cancers.…”
Section: Delivery Of Immunotherapeuticsmentioning
confidence: 99%